Tourism in Antarctica : a multidisciplinary view of new activities carried out on the white continent /: a multidisciplinary view of new activities carried out on the white continent. (2016) - Schillat, Monika, 1960-; Jensen, Marie; Vereda, Marisol; Sanchez, Rodolfo A; Roura, Ricardo
No abstract available